Analysis of the Impact of Culture in Practicing Islamic Values on the Development of Micro Businesses in Panekan District - Yana Dwi Christianti (International Journal of Social Science and Community Service, 2024)
Many Indonesian traditions have an Islamic nuance and are usually carried out to commemorate major Islamic holidays. For example, the Sekaten celebration is held to welcome the Prophet Muhammad’s birthday. During the month of Ramadan, there is also a tradition of welcoming the holy month with a slametan (known as unggahan poso), followed by another slametan to celebrate Eid al-Fitr. The Eid celebration typically lasts two to three days, beginning with the Sholat Ied (Eid prayer) on the first morning. During this time, Muslims greet each other with handshakes and formal embraces as a way of sharing joy and seeking forgiveness for past mistakes.Beyond that, the tradition of silaturahmi (visiting relatives and neighbors) is also practiced, with families serving sweet treats and giving gifts, especially to children and those in need. The presence of Indonesian traditions that embody Islamic values influences the growth of local micro-businesses. This is particularly evident during major Islamic holidays when deeply rooted traditions create a surge in demand. In Panekan Regency, this phenomenon significantly impacts the development of micro-enterprises during Ramadan and Eid al-Fitr.